Guía de práctica clínica basada en la evidencia para el manejo de la sedoanalgesia en el paciente adulto críticamente enfermo - Celis-Rodríguez, Edgar (2013)
ABSTRACT Introduction Optimal management of sedation, analgesia and delirium offers comfort and security for the critical care patient, allows support measures to be applied more easily and enables an integral approach of medical care, but at the same time lowers the incidence of complications, which translates in better patient outcomes. Objective To update the Guía de práctica clínica basada en la evidencia para el manejo de la sedoanalgesia en el paciente adulto críticamente enfermo published in Medicina Intensiva in 2007, and give recommendations for the management of sedation, analgesia, and delirium. Methodology A group of 21 intensivists from 9 countries of the Federación Panamericana e Ibérica de Sociedades de Medicina Crítica y Terapia Intensiva, 3 of them also specialists in clinical epidemiology and methodology, gathered for the development of guidelines. Assessment of evidence quality and recommendations were made based on the Grading of Recommendations Assessment, Development and Evaluation system. Strength of recommendations was classified as 1=strong, or 2=weak, and quality of evidence as A=high, B=moderate, or C=low. Two authors searched the following databases: MEDLINE through PUBMED, The Cochrane Library and Literatura Latinoamericana y del Caribe en Ciencias de la Salud and retrieved pertinent information. Members assigned to the 11 sections of the guidelines, based on the literature review, formulated the recommendations that were discussed in plenary sessions. Only those recommendations that achieved more than 80% of consensus were approved for the final document. The Colombian Association of Critical Medicine and Intensive Care (AMCI) supported the elaboration of these guidelines. Results Four hundred and sixty-seven articles were included for review. An increase in number and quality of publications was observed. This allowed to generate 64 strong recommendations with high and moderate quality of evidence in contrast to the 28 recommendations of the previous edition. Conclusions This guidelines contains recommendations and suggestions based on the best evidence available for the management of sedation, analgesia and delirium of the critically ill patient, including a bundle of strategies that serves this purpose. We highlight the assessment of pain and agitation/sedation through validated scales, the use of opioids initially to appropriate analgesic control, associated with multimodal strategies in order to reduce opioide consumption; to promote the lowest level of sedation necessary avoiding over-sedation. Also, in case of the need of sedatives, choose the most appropriate for the patient needs, avoiding the use of benzodiazepines and identify risk factors for delirium, in order to prevent its occurrence, diagnose delirium and treat it with the most suitable pharmacological agent, whether it is haloperidol, atypical antipsychotics or dexmedetomidine, once again, avoiding the use of benzodiazepines and decreasing the use of opioids.